2021
DOI: 10.3390/earth2010007
|View full text |Cite
|
Sign up to set email alerts
|

Localize the Impact of Global Greenhouse Gases Emissions under an Uncertain Future: A Case Study in Western Cape, South Africa

Abstract: The growing impact of CO2 and other greenhouse-gas (GHG) emissions on the socio-climate system in the Western Cape, South Africa, urgently calls for the need for better climate adaptation and emissions-reduction strategies. While the consensus has been that there is a strong correlation between CO2 emissions and the global climate system, few studies on climate change in the Western Cape have quantified the impact of climate change on local climate metrics such as precipitation and evaporation under different … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 27 publications
(31 reference statements)
0
4
0
Order By: Relevance
“…Climate change has become a severe problem for the modern world. Extensive studies have found that climate change can influence every aspect of society, from community vulnerability and resilience [1][2][3][4] to fresh water and climate ecosystems [5][6][7][8][9]. To address the climate crisis, electric vehicles (EVs) have been adopted worldwide to help fight climate change by reducing emissions compared to conventional gasoline vehicles (CVs) [7,10].…”
Section: Introductionmentioning
confidence: 99%
“…Climate change has become a severe problem for the modern world. Extensive studies have found that climate change can influence every aspect of society, from community vulnerability and resilience [1][2][3][4] to fresh water and climate ecosystems [5][6][7][8][9]. To address the climate crisis, electric vehicles (EVs) have been adopted worldwide to help fight climate change by reducing emissions compared to conventional gasoline vehicles (CVs) [7,10].…”
Section: Introductionmentioning
confidence: 99%
“…The results are well aligned with the previous studies by Naik and Abiodun [23], of which the projected changes in drought characteristics over the Western Cape show a robust drying signal under the RCP 8.5 emission scenario. Furthermore, He and Ding [14] also demonstrated that great potential of reducing climate risks and vulnerability exists in lowering GHG emissions for Western Cape region. Besides, by directly investigating extreme weather indices such as drought indices like CDD and heatwave indices like WSDI, this study better illustrates how emission reduction will protect the region's socio-economic systems by alleviating future extreme climate stress.…”
Section: Spatial-temporal Patterns Of Drought Indicesmentioning
confidence: 99%
“…Many studies that focused on the regional future climate risks such as drought only used simple climate characteristics such as precipitation and maximum surface air temperature to evaluate climate risk, overlooking the role of extreme events' impact on the region's social-economic system. For example, He and Ding [14] used a high-resolution GCM-RCM Coordinated Regional Downscaling Experiment Simulations (CORDEX) model chain to highlight the impact of GHG emissions on Western Cape's local climate system. They stressed that efficient water-management practices and GHG emissions reduction strategies are vital to mitigate more severe droughts such as the "Day-Zero" crisis in 2018, especially for the City of Cape Town and several other coastal regions within the Overberg and Eden district.…”
Section: Introductionmentioning
confidence: 99%
“…There is a rich amount of research [ 90 , 101 , 105 , 106 ] that has documented cases of climate initiatives that turned to maladaptation by undermining local access to resources, land rights, or community solidarity, or by limiting the choices of future generations. For example, to optimize production efficiency to climate variability, the introduction of new crop species and varieties is often mentioned by farmers as an adaptation measure in the agricultural adaptation literature [ 52 , 151 , 152 ]. Changing crops may have unexpected outcomes such as higher input of fertilizers, increased risk of pests, and weed infestations [ 99 ].…”
Section: The Science-based Climate Change Topics: a Literature Reviewmentioning
confidence: 99%